Fundamental Movement Skills and Moods as Predictors of Games Performance in Primary School Students - Ricky Wibowo; Eka Nugraha; Kuston Sultoni (Universitas Negeri Semarang, 2018)
The purpose of this study was to determine how far FMS and mood contribute toward games performance on elementray school student through invasion games activities (modified soccer and handball games). This research uses a correlational explanatory and regression . Third grade elementary school students (n=40) were enrolled in this study consisting of 21 male students and 19 female students. To determine the games perfromance using The Games Performance Assessment Instrument (GPAI) and Brief Mood Introspection Scale (BMIS) to measure the mood of the students. The increase in FMS of 0.005 units will predict the increase in the variable SB by 0.005, then the increase in the positive mood of 0.43 will predict the increase in the variable of 0.43 units, while the increase in negative mood variable of 0.030 will predict a decline in the SB variable of 0.030. The result showed that FMS and positive moods contributed toward games performance on both games.